THE EFFECTIVENESS OF THE STRATEGY (PQ5R) IN THE ACHIEVEMENT OF SECOND-GRADE INTERMEDIATE STUDENTS, IN THE SUBJECT OF SOCIAL STUDIES AND THEIR GENERATIVE THINKING - M.D. Yasser Abdul Wahid Hamid (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The research aims to identify the effectiveness of the PQ5R strategy in: Improving the achievement of second-grade intermediate students in the subject of social studies. Acquiring generative thinking skills for second-grade students when teaching social studies. This sample of the research included (62) students, distributed into two experimental and controlling groups, and each group contained (31) students. The two groups were equal in terms of (age, intelligence, previous educational achievement, general average grade, and generative pre-thinking). An achievement test was prepared containing (40) paragraphs, of a multiple-choice type and a generative thinking test consisting of (30) paragraphs, distributed into five areas: (the skill of developing hypotheses, the skill of prediction in light of the given data, the skill of recognizing errors and fallacies, the fluency skill, and the skill of flexibility). The results have shown that: There was a statistically significant difference at (0.05) between the averages of the two experimental groups that were studied with the strategy (PQ5R), and the controlling group that studied in the usual way in the achievement test and the generative thinking test, in favor of the experimental group. The researcher also concluded that teaching geography while using the strategy (PQ5R), increases the students' academic achievement better than with the traditional method, as well as increasing the students’ generative thinking.